Head First C#, 4th Edition - Greene, Jennifer; Stellman, Andrew (O'Reilly Media, Inc., 2020)
What will you learn from this book? Ready to dive into C#? This practical guide provides beginning programmers with a fun and highly visual introduction to C#, XAML, .NET Core, and Visual Studio. You'll quickly learn C# fundamentals, including how this language helps you create user interfaces, databases, and more. With this latest edition, you'll build a fully functional game in the opening chapter and then learn how to use classes and object-oriented programming, draw graphics and animation, and query data with LINQ. And you'll do it all by creating games, solving puzzles, and doing hands-on projects. By the time you're done, you'll be a solid C# programmer-and you'll have a great time along the way! Dive right in-build a game with C# in the first chapter Learn how to use XAML to design attractive and interactive pages and windows Use any edition of Visual Studio to practice your C# coding skills in dozens of projects Create cross-platform apps and build native macOS apps using Visual Studio 2019 for Mac Develop 3D games and simulations in specially designed Unity labs using C# tools, techniques, and concepts Why does this book look so different? Based on the latest research in cognitive science and learning theory, Head First C# uses a visually rich format to engage your mind rather than a text-heavy approach that puts you to sleep. Why waste your time struggling with new concepts? This multisensory learning experience is designed for the way your brain really works.
Online resource; Title from title page (viewed December 25, 2020)